Method for heavy metal stabilization and solidification of desulfurization gypsum residue
Patent Information
- Application Number
- CN202611300843.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-16
AI Technical Summary
该方法工艺简单、成本较低,但存在如下缺陷:固化体孔隙率较高;在长期酸雨或地下水环境中易发生重金属再浸出;对Hg、Cd等两性或挥发性重金属稳定效果有限;水泥掺量较大,导致处理成本升高及资源化利用受限
[0056] 1. This invention can significantly reduce the leaching concentration of heavy metals such as Pb, Cd, and Hg through the synergistic effect of sulfurization stabilizers and organic chelating agents, with the Pb leaching reduction rate exceeding 95%.
Abstract
Description
Technical Field
[0001] This invention relates to the field of industrial solid waste resource utilization and environmental remediation technology, and in particular to a method for stabilizing and solidifying heavy metals in desulfurized gypsum slag. Background Technology
[0002] Desulfurization gypsum is a major industrial byproduct generated during flue gas desulfurization processes in coal-fired power plants, steel sintering, non-ferrous metal smelting, and chemical industries. Its main component is calcium sulfate dihydrate (CaSO4·2H2O). With the continuous advancement of my country's ultra-low emission policy and the expanding scale of industrial flue gas treatment, the annual production of desulfurization gypsum has been steadily increasing, with annual emissions in some regions exceeding ten million tons. Due to the complexity of desulfurization raw materials, significant differences in flue gas sources, and the enrichment of impurities in the absorption system, desulfurization gypsum slag typically contains heavy metals such as Pb, Cd, Cr, Hg, As, and Se, as well as harmful impurities such as chloride salts and fluoride salts.
[0003] Currently, a large amount of desulfurization gypsum slag is still disposed of through stockpiling, landfilling, or low-value utilization. Because desulfurization gypsum itself has a certain degree of solubility, heavy metal ions are prone to migration and leaching under conditions of rainwater leaching, groundwater soaking, or acidic environments, causing soil and groundwater pollution and posing significant environmental risks. Therefore, how to achieve long-term stabilization and resource utilization of heavy metals in desulfurization gypsum slag has become an important research direction in the field of industrial solid waste treatment.
[0004] In existing technologies, the following types of treatment methods are mainly used for desulfurization gypsum or similar industrial gypsum waste containing heavy metals:
[0005] (1) Cement solidification method: Traditional technology usually uses ordinary silicate cement to solidify waste slag containing heavy metals. The CSH gel formed by cement hydration physically encapsulates and adsorbs the heavy metals. This method is simple and low in cost, but it has the following drawbacks: the solidified body has high porosity; heavy metals are prone to re-leaching in long-term acid rain or groundwater environments; the stabilizing effect on amphoteric or volatile heavy metals such as Hg and Cd is limited; and the cement content is large, which leads to increased treatment costs and limited resource utilization.
[0006] For example, patent CN105130363A, "A Method for Permanent Solidification of Heavy Metal Waste", proposes a method for permanent solidification of heavy metal waste using a cement system. However, this technology mainly relies on a highly alkaline gelling system for coating, and there is still a risk of leaching in the later stages.
[0007] Furthermore, some studies have indicated that Hg in highly alkaline environments... 2 ⁺ It is easy to form precipitates such as HgO, which may redissolve in porous cement systems, thus affecting long-term stability.
[0008] (2) Single sulfide stabilization method: In order to reduce the solubility of heavy metal ions such as Pb, Cd, and Hg, some technologies use sulfiding agents such as sodium sulfide and thiosulfate to form sulfide precipitates with low solubility of heavy metals.
[0009] For example, patent CN101746934A, "Method for Stabilizing and Fixing Cadmium in Heavy Metal Pollutant Deposits Using Flue Gas Desulfurization Gypsum", proposes a method for stabilizing Cd pollutant deposits using flue gas desulfurization gypsum.
[0010] While sulfide stabilization can rapidly reduce the leaching concentration of some heavy metals, it still presents several problems: single sulfides are susceptible to oxidation; heavy metals may be released again after long-term exposure; the solidified body has low mechanical strength; and it is difficult to meet the requirements for engineering resource utilization. Therefore, relying solely on sulfide precipitation is insufficient to simultaneously ensure long-term stability and structural strength.
[0011] (3) Chemical chelation and geopolymerization method
[0012] In recent years, some studies have begun to use organosulfur chelating agents or geopolymer systems to stabilize heavy metals.
[0013] For example, patent CN103641346A, "A method for preparing geopolymer cementitious materials using heavy metal gypsum", proposes a method for preparing geopolymer cementitious materials using heavy metal gypsum, slag and alkali activator.
[0014] For example, patent CN103495271A, "A Method for Harmless Treatment of Heavy Metal Gypsum Composite System," proposes a method for harmless treatment of heavy metal gypsum using a composite stabilization system.
[0015] While the above methods can improve the fixation effect of heavy metals, they still have the following shortcomings: the geopolymer system has high alkalinity, which can easily lead to the reactivation of some amphoteric heavy metals; the cost of activators is high; the process stability is greatly affected by the fluctuation of raw materials; and some processes require high-temperature calcination, resulting in high energy consumption.
[0016] (4) Pretreatment and resource utilization technology of desulfurized gypsum
[0017] To reduce the impurities and heavy metal content in desulfurized gypsum, some technologies employ pretreatment methods such as acid washing, oxidation, and ball milling.
[0018] For example, patent CN118545927A, "Method for Pretreatment of Desulfurized Gypsum", proposes a method to reduce the heavy metals and moisture content in desulfurized gypsum through ball milling, acid washing, oxidation, and organic alcohol treatment.
[0019] In addition, patent CN109231859B, "A Method for Resource Utilization Treatment of Arsenic-Containing Desulfurized Gypsum Slag", proposes a method for roasting and resource utilization treatment of arsenic-containing desulfurized gypsum slag.
[0020] However, the above technologies generally suffer from problems such as: complex process flow; high energy consumption; difficulty in treating secondary waste liquid; and difficulty in achieving low-cost large-scale promotion and application.
[0021] In addition, previous studies have shown that the gypsum-slag-fly ash system can form a large amount of ettringite (AFt) and CSH gel structure under alkaline activation conditions, which can effectively adsorb and encapsulate heavy metal ions, thereby reducing their migration.
[0022] Therefore, developing a method for stabilizing and solidifying heavy metals in desulfurized gypsum slag that combines: sulfide precipitation stabilization; organic chelation fixation; gelling mineralization coating; high strength and low leaching characteristics; and is simple, cost-effective, and suitable for continuous industrial operation has significant engineering application value and environmental significance. Summary of the Invention
[0023] Based on the problems raised in the background technology mentioned above, this invention proposes a method for stabilizing and solidifying heavy metals in desulfurized gypsum slag.
[0024] The technical solution is as follows:
[0025] A method for stabilizing and solidifying heavy metals in desulfurized gypsum slag includes the following steps:
[0026] (1) Preprocessing steps:
[0027] By weight, 100 parts of desulfurized gypsum slag were crushed, screened, and dried at low temperature. The particle size of the desulfurized gypsum slag was controlled to be 0.05-2 mm and the moisture content was 8-15%. The calcium sulfate dihydrate content in the desulfurized gypsum slag was 55-85 wt%.
[0028] (2) Preparation steps of the gel stabilization system:
[0029] By weight, 18-32 parts of granulated blast furnace slag powder, 8-18 parts of fly ash, 4-10 parts of silicate cement, and 1.5-4 parts of quicklime are added to the desulfurized gypsum slag and mixed.
[0030] (3) Heavy metal sulfidation stabilization steps:
[0031] By weight, add 0.8 to 2.5 parts of sodium sulfide and 0.3 to 1.2 parts of sodium thiosulfate as sulfide stabilizers, and then add 0.1 to 0.5 parts of sulfide stabilizing synergist.
[0032] (4) Chelation and curing step:
[0033] Add 0.3 to 1.5 parts by weight of an organic sulfur chelating agent, wherein the organic sulfur chelating agent is selected from one or more of sodium dithiocarbamate, trithiotriazine trisodium salt TMT-15, and sodium mercaptoacetate.
[0034] (5) Alkali activation and mixing steps:
[0035] Add 2-6 parts by weight of alkali activator and 18-30 parts by weight of water and mix. Control the pH of the slurry to be 9.5-11.8, the stirring speed to be 25-60 rpm, and the stirring time to be 15-40 min.
[0036] (6) Aging and curing steps:
[0037] The obtained slurry is aged at 20-35℃ for 4-18 hours, and then pressed into shape or naturally stacked.
[0038] (7) Maintenance steps:
[0039] The desulfurized gypsum slag was cured at 25–55℃ and 70–95% relative humidity for 3–14 days to obtain a stable solidified product of heavy metals.
[0040] In some embodiments, the desulfurized gypsum slag originates from one or more of the following systems: limestone-gypsum wet desulfurization system of coal-fired power plant, flue gas desulfurization system of iron and steel sintering, or flue gas desulfurization system of non-ferrous metal smelting; the desulfurized gypsum slag contains 50-800 mg / kg of Pb, 5-120 mg / kg of Cd, and 20-500 mg / kg of Cr.
[0041] In some embodiments, the granulated blast furnace slag powder has a specific surface area of 380–520 m². 2 / kg, with an activity index of 95-110%; the fly ash is Class II fly ash, with a total SiO2 and Al2O3 content of 65-88wt%.
[0042] In some embodiments, the silicate cement is P.O42.5 ordinary silicate cement or P.SA32.5 slag silicate cement; the CaO content in the quicklime is not less than 85wt%.
[0043] In some embodiments, the sodium sulfide is Na2S·9H2O with a purity ≥60wt%; the sodium thiosulfate is Na2S2O3·5H2O with a purity ≥98wt%.
[0044] In some embodiments, the method for preparing the vulcanization stabilizer is as follows:
[0045] By weight, 29-53 parts of triethylenetetramine distillation residue (main component: triethylenetetramine, containing primary and secondary amine active functional groups, produced by a company in Zhejiang) and 145-265 parts of acrylate industrial wastewater (mass concentration 7%-11%, main component: calcium acrylate, containing carbon-carbon double bonds and carboxylate functional groups, produced by a company in Zhejiang) were mixed evenly. 0.12-0.55 parts of sodium bicarbonate were added as a weak base addition catalyst, and the mixture was stirred and reacted at a constant temperature of 58-78℃ for 70-100 min. After the reaction, the mixture was dried under vacuum at a constant temperature and ground at room temperature to obtain the sulfide stabilizing synergist.
[0046] In some embodiments, the sodium dithiocarbamate has a purity of 85–98 wt%; the trisodium trithiotriazine content in TMT-15 is 12–18 wt%.
[0047] In some embodiments, the alkali activator is selected from one or more of water glass, sodium hydroxide, and sodium carbonate with a modulus of 2.0 to 3.3.
[0048] In some embodiments, the liquid-to-solid ratio of the slurry in step (5) is controlled to be 0.18 to 0.30; the slurry temperature is controlled to be 20 to 45°C during stirring; and the slurry slump expansion is controlled to be 160 to 260 mm.
[0049] In some embodiments, the pressing pressure in step (6) is 3 to 12 MPa; the water content of the system is controlled to be 18 to 28 wt% during aging; and the porosity of the solidified body is controlled to be 15 to 35% after aging.
[0050] Reaction mechanism:
[0051] This invention addresses the challenges of complex heavy metal composition, easy leaching, and poor solidification stability in desulfurized gypsum slag. It constructs a multi-stage synergistic stabilization and solidification system comprising composite gelation coating, sulfide precipitation fixation, organic chelation deep solidification, and alkali-activated densification modification. This system achieves long-term stable solidification of multiple heavy metals in desulfurized gypsum slag and improves the resource utilization of solid waste. Firstly, the desulfurized gypsum slag undergoes crushing, screening, and low-temperature drying pretreatment to optimize particle size and moisture content, homogenize material composition, and eliminate interference from impurities and moisture on subsequent solidification reactions, providing favorable material conditions for gelation and heavy metal stabilization reactions.
[0052] This process employs a composite cementitious system made from slag powder, fly ash, silicate cement, and quicklime. Under alkaline activation conditions, a hydration reaction occurs, continuously generating dense hydration products such as CSH gel and ettringite. These products gradually fill the internal pores of the material, building a stable and dense three-dimensional network cementitious structure. This physically encapsulates and fixes heavy metal ions, significantly reducing the migration and leaching channels for heavy metals and improving the overall density and structural stability of the solidified body. The alkaline environment within the system can regulate the form of heavy metals and inhibit the activation and dissolution of heavy metal ions.
[0053] The core of heavy metal stabilization relies on the synergistic effect of a sulfurization composite system and a specialized sulfurization stabilizing synergist. The sulfurization stabilizer, a combination of sodium sulfide and sodium thiosulfate, releases active sulfur ions in an alkaline system. These ions combine with heavy metal ions such as lead, cadmium, chromium, and mercury to form sparingly soluble metal sulfide precipitates with extremely low solubility, thus achieving initial fixation of heavy metals. The self-prepared sulfide stabilizing synergist is the core functional additive. Among them, the triethylenetetramine distillation residue contains abundant primary and secondary amine active functional groups, which have excellent complexation adsorption and dispersion activation capabilities. It can adsorb free heavy metal ions in the system, activate the sulfide reaction activity, improve the dispersibility of sulfide agents, and prevent the aggregation and failure of sulfide products. The carbon-carbon double bonds and carboxylate functional groups contained in acrylate industrial wastewater can undergo cross-linking polymerization under weak alkaline catalysis to form a flexible organic polymer network, which encapsulates and anchors sulfide precipitates, blocks micropores, and further blocks the leaching pathway of heavy metals. Sodium bicarbonate, as a weak alkaline catalyst, can mildly regulate the reaction environment of the system, promote the addition cross-linking reaction of amine groups and carboxylate groups, and improve the overall structural stability and compatibility of the synergist.
[0054] Building upon this foundation, organic sulfur chelating agents can capture residual trace amounts of free heavy metal ions within the system, forming highly stable cyclic chelates through chelation coordination. This overcomes the limitations of single sulfurization curing, achieving deep curing of heavy metals. Finally, precise aging and constant temperature and humidity curing ensure the full progress of the gelation hydration reaction, sulfurization precipitation reaction, and organic chelation reaction. This allows multiple mechanisms—physical coating, chemical precipitation, and complexation curing—to work synergistically, ultimately yielding a dense, solidified desulfurized gypsum slag product with excellent heavy metal stability.
[0055] Compared with the prior art, the present invention has the following advantages:
[0056] 1. This invention can significantly reduce the leaching concentration of heavy metals such as Pb, Cd, and Hg through the synergistic effect of sulfurization stabilizers and organic chelating agents, with the Pb leaching reduction rate exceeding 95%.
[0057] 2. The present invention adopts a slag powder-fly ash-cement composite cementitious system, which can form a dense CSH gel and ettringite crystal structure, thereby improving the density and long-term stability of the solidified body.
[0058] 3. The process conditions of this invention are mild, and there is no need for high-temperature sintering. It has the advantages of low energy consumption, low cost and suitability for continuous industrial applications.
[0059] 4. This invention realizes the resource utilization of desulfurized gypsum slag, reduces the amount of industrial solid waste stockpiles, and has good environmental and economic benefits. Detailed Implementation
[0060] The features of the present invention are further illustrated below through embodiments, but the scope of protection of this patent is not limited to the embodiments.
[0061] Example 1
[0062] (1) Pretreatment steps
[0063] 100 kg of desulfurized gypsum slag was crushed, screened, and dried at low temperature to control the particle size of the desulfurized gypsum slag to be 0.05 mm and the moisture content to be 8%. The content of calcium sulfate dihydrate in the desulfurized gypsum slag was 55 wt%. The desulfurized gypsum slag came from the limestone-gypsum wet desulfurization system of a coal-fired power plant. The content of Pb in the desulfurized gypsum slag was 50 mg / kg, the content of Cd was 5 mg / kg, and the content of Cr was 20 mg / kg.
[0064] (2) Preparation steps of the gel stabilization system
[0065] 18 kg of granulated blast furnace slag powder, 8 kg of fly ash, 4 kg of silicate cement, and 1.5 kg of quicklime were added to the desulfurized gypsum slag and mixed; the granulated blast furnace slag powder had a specific surface area of 380 m². 2 / kg, with an activity index of 95%; the fly ash is Grade II fly ash, with a total SiO2 and Al2O3 content of 65wt%; the silicate cement is P.O42.5 ordinary silicate cement; the quicklime contains not less than 85wt% CaO.
[0066] (3) Heavy metal sulfidation stabilization steps
[0067] Add 0.8 kg of sodium sulfide and 0.3 kg of sodium thiosulfate as sulfide stabilizers, and then add 0.1 kg of sulfide stabilizing enhancer; the sodium sulfide is Na2S·9H2O with a purity ≥60wt%; the sodium thiosulfate is Na2S2O3·5H2O with a purity ≥98wt%.
[0068] The preparation method of the sulfur stabilizing synergist is as follows: 29 kg of triethylenetetramine distillation residue is mixed evenly with 145 kg of acrylate industrial wastewater (mass concentration 7%), and 0.12 kg of sodium bicarbonate is added as a weak base addition catalyst. The mixture is stirred and reacted at a constant temperature of 58℃ for 70 min. After the reaction is completed, the mixture is dried under vacuum at a constant temperature and ground at room temperature to obtain the sulfur stabilizing synergist.
[0069] (4) Chelation and curing steps
[0070] Add 0.3 kg of organic sulfur chelating agent, wherein the organic sulfur chelating agent is selected from sodium dithiocarbamate, and the purity of sodium dithiocarbamate is 85 wt%.
[0071] (5) Alkali activation and mixing steps
[0072] Add 2kg of alkali activator and 18kg of water and mix and stir, control the pH of the slurry to 9.5, the stirring speed to 25rpm, and the stirring time to 15min; the alkali activator is selected from water glass with a modulus of 2.0; the liquid-solid ratio of the slurry in step (5) is controlled to be 0.18; the temperature of the slurry during the stirring process is controlled to be 20℃; the slump expansion of the slurry is controlled to be 160mm.
[0073] (6) Aging and curing steps
[0074] The obtained slurry was aged at 20°C for 4 hours and then naturally stacked. During the aging process, the water content of the system was controlled at 18 wt%. After the aging was completed, the porosity of the solidified body was controlled at 15%.
[0075] (7) Maintenance steps
[0076] The desulfurized gypsum slag was cured at 25℃ and 70% relative humidity for 3 days to obtain a stable solidified product of heavy metals.
[0077] Example 2
[0078] (1) Pretreatment steps
[0079] 100 kg of desulfurized gypsum slag was crushed, screened, and dried at low temperature to control the particle size of the desulfurized gypsum slag to be 0.6 mm and the moisture content to be 11%. The content of calcium sulfate dihydrate in the desulfurized gypsum slag was 70 wt%. The desulfurized gypsum slag came from the desulfurization system of iron and steel sintering flue gas. The content of Pb in the desulfurized gypsum slag was 400 mg / kg, the content of Cd was 60 mg / kg, and the content of Cr was 260 mg / kg.
[0080] (2) Preparation steps of the gel stabilization system
[0081] 25 kg of granulated blast furnace slag powder, 13 kg of fly ash, 7 kg of silicate cement, and 2.8 kg of quicklime were added to the desulfurized gypsum slag and mixed; the granulated blast furnace slag powder had a specific surface area of 450 m². 2 / kg, with an activity index of 102%; the fly ash is Grade II fly ash, with a total SiO2 and Al2O3 content of 76wt%; the silicate cement is P.SA32.5 slag silicate cement; the quicklime contains no less than 85wt% CaO.
[0082] (3) Heavy metal sulfidation stabilization steps
[0083] 1.6 kg of sodium sulfide and 0.7 kg of sodium thiosulfate were added as sulfide stabilizers, and 0.3 kg of sulfide stabilizing enhancer was added; the sodium sulfide was Na2S·9H2O with a purity ≥60wt%; the sodium thiosulfate was Na2S2O3·5H2O with a purity ≥98wt%.
[0084] The preparation method of the sulfur stabilizing synergist is as follows: 41 kg of triethylenetetramine distillation residue is mixed evenly with 205 kg of acrylate industrial wastewater (mass concentration 9%), and 0.33 kg of sodium bicarbonate is added as a weak base addition catalyst. The mixture is stirred and reacted at a constant temperature of 68℃ for 85 min. After the reaction is completed, the mixture is dried under vacuum at a constant temperature and ground at room temperature to obtain the sulfur stabilizing synergist.
[0085] (4) Chelation and curing steps
[0086] Add 0.9 kg of organic sulfur chelating agent, wherein the organic sulfur chelating agent is selected from trithiotriazine trisodium salt TMT-15, and the content of trithiotriazine trisodium salt in TMT-15 is 15 wt%.
[0087] (5) Alkali activation and mixing steps
[0088] Add 4 kg of alkali activator and 24 kg of water and mix and stir. Control the pH of the slurry to 10.6, the stirring speed to 40 rpm, and the stirring time to 28 min. The alkali activator is selected from sodium hydroxide. The liquid-solid ratio of the slurry in step (5) is controlled to be 0.24. The temperature of the slurry during stirring is controlled to be 32℃. The slump expansion of the slurry is controlled to be 210 mm.
[0089] (6) Aging and curing steps
[0090] The obtained slurry was aged at 28℃ for 11 hours and then pressed into shape at a pressure of 7MPa. The water content of the system was controlled at 23wt% during the aging process. The porosity of the solidified body was controlled at 25% after aging.
[0091] (7) Maintenance steps
[0092] The desulfurized gypsum slag was cured at 40℃ and 82% relative humidity for 8 days to obtain a stable solidified product of heavy metals.
[0093] Example 3
[0094] (1) Pretreatment steps
[0095] 100 kg of desulfurized gypsum slag was crushed, screened, and dried at low temperature to control the particle size of the desulfurized gypsum slag to be 1.2 mm and the moisture content to be 13%. The content of calcium sulfate dihydrate in the desulfurized gypsum slag was 78 wt%. The desulfurized gypsum slag came from the desulfurization system of non-ferrous metal smelting flue gas. The content of Pb in the desulfurized gypsum slag was 600 mg / kg, the content of Cd was 90 mg / kg, and the content of Cr was 380 mg / kg.
[0096] (2) Preparation steps of the gel stabilization system
[0097] 29 kg of granulated blast furnace slag powder, 16 kg of fly ash, 8.5 kg of silicate cement, and 3.4 kg of quicklime were added to the desulfurized gypsum slag and mixed; the granulated blast furnace slag powder had a specific surface area of 490 m². 2 / kg, with an activity index of 106%; the fly ash is Grade II fly ash, with a total SiO2 and Al2O3 content of 82wt%; the silicate cement is a blend of P.O42.5 ordinary silicate cement and P.SA32.5 slag silicate cement; the quicklime contains no less than 85wt% CaO.
[0098] (3) Heavy metal sulfidation stabilization steps
[0099] 2.1 kg of sodium sulfide and 1.0 kg of sodium thiosulfate were added as sulfide stabilizers, and 0.4 kg of sulfide stabilizing enhancer was added; the sodium sulfide was Na2S·9H2O with a purity ≥60wt%; the sodium thiosulfate was Na2S2O3·5H2O with a purity ≥98wt%.
[0100] The preparation method of the sulfur stabilizing synergist is as follows: 48 kg of triethylenetetramine distillation residue is mixed evenly with 240 kg of acrylate industrial wastewater (mass concentration 10%), and 0.45 kg of sodium bicarbonate is added as a weak base addition catalyst. The mixture is stirred and reacted at a constant temperature of 73℃ for 92 min. After the reaction is completed, the mixture is dried under vacuum at a constant temperature and ground at room temperature to obtain the sulfur stabilizing synergist.
[0101] (4) Chelation and curing steps
[0102] Add 1.2 kg of organic sulfur chelating agent, wherein the organic sulfur chelating agent is selected from sodium mercaptoacetate and trithiotriazine trisodium salt TMT-15, and the content of trithiotriazine trisodium salt in TMT-15 is 17 wt%.
[0103] (5) Alkali activation and mixing steps
[0104] Add 5 kg of alkali activator and 27 kg of water and mix and stir. Control the pH of the slurry to 11.2, the stirring speed to 50 rpm, and the stirring time to 35 min. The alkali activator is selected from sodium carbonate. The liquid-solid ratio of the slurry in step (5) is controlled to be 0.27. The temperature of the slurry during stirring is controlled to be 38℃. The slump expansion of the slurry is controlled to be 240 mm.
[0105] (6) Aging and curing steps
[0106] The obtained slurry was aged at 32℃ for 14 hours, and then pressed into shape at a pressure of 10MPa. The water content of the system was controlled at 26wt% during the aging process. After aging, the porosity of the solidified body was controlled at 30%.
[0107] (7) Maintenance steps
[0108] The desulfurized gypsum slag was cured at 48℃ and 88% relative humidity for 11 days to obtain a stable solidified product of heavy metals.
[0109] Example 4
[0110] (1) Pretreatment steps
[0111] 100 kg of desulfurized gypsum slag was crushed, screened, and dried at low temperature to control the particle size of the desulfurized gypsum slag to be 2 mm and the moisture content to be 15%. The content of calcium sulfate dihydrate in the desulfurized gypsum slag was 85 wt%. The desulfurized gypsum slag was derived from mixed raw materials of flue gas desulfurization systems in coal-fired power plants, iron and steel sintering, and non-ferrous metal smelting. The content of Pb in the desulfurized gypsum slag was 800 mg / kg, the content of Cd was 120 mg / kg, and the content of Cr was 500 mg / kg.
[0112] (2) Preparation steps of the gel stabilization system
[0113] 32 kg of granulated blast furnace slag powder, 18 kg of fly ash, 10 kg of silicate cement, and 4 kg of quicklime were added to the desulfurized gypsum slag and mixed; the granulated blast furnace slag powder had a specific surface area of 520 m². 2 / kg, with an activity index of 110%; the fly ash is Grade II fly ash, with a total SiO2 and Al2O3 content of 88wt%; the silicate cement is P.O42.5 ordinary silicate cement; the quicklime contains no less than 85wt% CaO.
[0114] (3) Heavy metal sulfidation stabilization steps
[0115] Add 2.5 kg of sodium sulfide and 1.2 kg of sodium thiosulfate as sulfide stabilizers, and then add 0.5 kg of sulfide stabilizing enhancer; the sodium sulfide is Na2S·9H2O with a purity ≥60wt%; the sodium thiosulfate is Na2S2O3·5H2O with a purity ≥98wt%.
[0116] The preparation method of the sulfur stabilizing synergist is as follows: 53 kg of triethylenetetramine distillation residue is mixed evenly with 265 kg of acrylate industrial wastewater (mass concentration 11%), and 0.55 kg of sodium bicarbonate is added as a weak base addition catalyst. The mixture is stirred and reacted at a constant temperature of 78°C for 100 min. After the reaction is completed, the mixture is dried under vacuum at a constant temperature and ground at room temperature to obtain the sulfur stabilizing synergist.
[0117] (4) Chelation and curing steps
[0118] Add 1.5 kg of organic sulfur chelating agent, wherein the organic sulfur chelating agent is selected from sodium dithiocarbamate, trithiotriazine trisodium salt TMT-15, and sodium mercaptoacetate. The purity of sodium dithiocarbamate is 98 wt%, and the content of trithiotriazine trisodium salt in TMT-15 is 18 wt%.
[0119] (5) Alkali activation and mixing steps
[0120] Add 6 kg of alkali activator and 30 kg of water and mix and stir. Control the pH of the slurry to 11.8, the stirring speed to 60 rpm, and the stirring time to 40 min. The alkali activator is selected from water glass, sodium hydroxide and sodium carbonate with a modulus of 3.3. The liquid-solid ratio of the slurry in step (5) is controlled to be 0.30. The temperature of the slurry during the stirring process is controlled to be 45℃. The slump expansion of the slurry is controlled to be 260 mm.
[0121] (6) Aging and curing steps
[0122] The obtained slurry was aged at 35℃ for 18 hours, and then pressed into shape at a pressure of 12MPa. The water content of the system was controlled at 28wt% during the aging process. The porosity of the solidified body was controlled at 35% after aging.
[0123] (7) Maintenance steps
[0124] The desulfurized gypsum slag was cured at 55℃ and 95% relative humidity for 14 days to obtain a stable solidified product of heavy metals.
[0125] Comparative Example 1
[0126] (1) Pretreatment steps
[0127] 100 kg of desulfurized gypsum slag was crushed, screened, and dried at low temperature to control the particle size of the desulfurized gypsum slag to be 0.05 mm and the moisture content to be 8%. The content of calcium sulfate dihydrate in the desulfurized gypsum slag was 55 wt%. The desulfurized gypsum slag came from the limestone-gypsum wet desulfurization system of a coal-fired power plant. The content of Pb in the desulfurized gypsum slag was 50 mg / kg, the content of Cd was 5 mg / kg, and the content of Cr was 20 mg / kg.
[0128] (2) Preparation steps of the gel stabilization system
[0129] 18 kg of granulated blast furnace slag powder, 8 kg of fly ash, 4 kg of silicate cement, and 1.5 kg of quicklime were added to the desulfurized gypsum slag and mixed; the granulated blast furnace slag powder had a specific surface area of 380 m². 2 / kg, with an activity index of 95%; the fly ash is Grade II fly ash, with a total SiO2 and Al2O3 content of 65wt%; the silicate cement is P.O42.5 ordinary silicate cement; the quicklime contains not less than 85wt% CaO.
[0130] (3) Heavy metal sulfidation stabilization steps
[0131] Add 0.8 kg of sodium sulfide and 0.3 kg of sodium thiosulfate as sulfide stabilizers; the sodium sulfide is Na2S·9H2O with a purity ≥60wt%; the sodium thiosulfate is Na2S2O3·5H2O with a purity ≥98wt%.
[0132] (4) Chelation and curing steps
[0133] Add 0.3 kg of organic sulfur chelating agent, wherein the organic sulfur chelating agent is selected from sodium dithiocarbamate, and the purity of sodium dithiocarbamate is 85 wt%.
[0134] (5) Alkali activation and mixing steps
[0135] Add 2kg of alkali activator and 18kg of water and mix and stir, control the pH of the slurry to 9.5, the stirring speed to 25rpm, and the stirring time to 15min; the alkali activator is selected from water glass with a modulus of 2.0; the liquid-solid ratio of the slurry in step (5) is controlled to be 0.18; the temperature of the slurry during the stirring process is controlled to be 20℃; the slump expansion of the slurry is controlled to be 160mm.
[0136] (6) Aging and curing steps
[0137] The obtained slurry was aged at 20°C for 4 hours and then naturally stacked. During the aging process, the water content of the system was controlled at 18 wt%. After the aging was completed, the porosity of the solidified body was controlled at 15%.
[0138] (7) Maintenance steps
[0139] The desulfurized gypsum slag was cured at 25℃ and 70% relative humidity for 3 days to obtain a stable solidified product of heavy metals.
[0140] Comparative Example 2
[0141] (1) Pretreatment steps
[0142] 100 kg of desulfurized gypsum slag was crushed, screened, and dried at low temperature to control the particle size of the desulfurized gypsum slag to be 0.05 mm and the moisture content to be 8%. The content of calcium sulfate dihydrate in the desulfurized gypsum slag was 55 wt%. The desulfurized gypsum slag came from the limestone-gypsum wet desulfurization system of a coal-fired power plant. The content of Pb in the desulfurized gypsum slag was 50 mg / kg, the content of Cd was 5 mg / kg, and the content of Cr was 20 mg / kg.
[0143] (2) Preparation steps of the gel stabilization system
[0144] 18 kg of granulated blast furnace slag powder, 8 kg of fly ash, 4 kg of silicate cement, and 1.5 kg of quicklime were added to the desulfurized gypsum slag and mixed; the granulated blast furnace slag powder had a specific surface area of 380 m². 2 / kg, with an activity index of 95%; the fly ash is Grade II fly ash, with a total SiO2 and Al2O3 content of 65wt%; the silicate cement is P.O42.5 ordinary silicate cement; the quicklime contains not less than 85wt% CaO.
[0145] (3) Heavy metal sulfidation stabilization steps
[0146] Add 0.8 kg of sodium sulfide and 0.3 kg of sodium thiosulfate as sulfide stabilizers, and then add 0.1 kg of sulfide stabilizing enhancer; the sodium sulfide is Na2S·9H2O with a purity ≥60wt%; the sodium thiosulfate is Na2S2O3·5H2O with a purity ≥98wt%.
[0147] The preparation method of the sulfur stabilizing synergist is as follows: 0.12 kg of sodium bicarbonate is added to 29 kg of triethylenetetramine distillation residue as a weak base addition catalyst, and the mixture is stirred and reacted at a constant temperature of 58°C for 70 min; after the reaction is completed, the mixture is dried under vacuum at a constant temperature and ground at room temperature to obtain the sulfur stabilizing synergist.
[0148] (4) Chelation and curing steps
[0149] Add 0.3 kg of organic sulfur chelating agent, wherein the organic sulfur chelating agent is selected from sodium dithiocarbamate, and the purity of sodium dithiocarbamate is 85 wt%.
[0150] (5) Alkali activation and mixing steps
[0151] Add 2kg of alkali activator and 18kg of water and mix and stir, control the pH of the slurry to 9.5, the stirring speed to 25rpm, and the stirring time to 15min; the alkali activator is selected from water glass with a modulus of 2.0; the liquid-solid ratio of the slurry in step (5) is controlled to be 0.18; the temperature of the slurry during the stirring process is controlled to be 20℃; the slump expansion of the slurry is controlled to be 160mm.
[0152] (6) Aging and curing steps
[0153] The obtained slurry was aged at 20°C for 4 hours and then naturally stacked. During the aging process, the water content of the system was controlled at 18 wt%. After the aging was completed, the porosity of the solidified body was controlled at 15%.
[0154] (7) Maintenance steps
[0155] The desulfurized gypsum slag was cured at 25℃ and 70% relative humidity for 3 days to obtain a stable solidified product of heavy metals.
[0156] Comparative Example 3
[0157] (1) Pretreatment steps
[0158] 100 kg of desulfurized gypsum slag was crushed, screened, and dried at low temperature to control the particle size of the desulfurized gypsum slag to be 0.05 mm and the moisture content to be 8%. The content of calcium sulfate dihydrate in the desulfurized gypsum slag was 55 wt%. The desulfurized gypsum slag came from the limestone-gypsum wet desulfurization system of a coal-fired power plant. The content of Pb in the desulfurized gypsum slag was 50 mg / kg, the content of Cd was 5 mg / kg, and the content of Cr was 20 mg / kg.
[0159] (2) Preparation steps of the gel stabilization system
[0160] 18 kg of granulated blast furnace slag powder, 8 kg of fly ash, 4 kg of silicate cement, and 1.5 kg of quicklime were added to the desulfurized gypsum slag and mixed; the granulated blast furnace slag powder had a specific surface area of 380 m². 2 / kg, with an activity index of 95%; the fly ash is Grade II fly ash, with a total SiO2 and Al2O3 content of 65wt%; the silicate cement is P.O42.5 ordinary silicate cement; the quicklime contains not less than 85wt% CaO.
[0161] (3) Heavy metal sulfidation stabilization steps
[0162] Add 0.8 kg of sodium sulfide and 0.3 kg of sodium thiosulfate as sulfide stabilizers, and then add 0.1 kg of sulfide stabilizing enhancer; the sodium sulfide is Na2S·9H2O with a purity ≥60wt%; the sodium thiosulfate is Na2S2O3·5H2O with a purity ≥98wt%.
[0163] The preparation method of the sulfurization stabilizing agent is as follows: 0.12 kg of sodium bicarbonate is added to 145 kg of acrylate industrial wastewater (mass concentration 7%) as a weak base addition catalyst, and the mixture is stirred and reacted at a constant temperature of 58℃ for 70 min; after the reaction is completed, the mixture is dried under vacuum at a constant temperature and ground at room temperature to obtain the sulfurization stabilizing agent.
[0164] (4) Chelation and curing steps
[0165] Add 0.3 kg of organic sulfur chelating agent, wherein the organic sulfur chelating agent is selected from sodium dithiocarbamate, and the purity of sodium dithiocarbamate is 85 wt%.
[0166] (5) Alkali activation and mixing steps
[0167] Add 2kg of alkali activator and 18kg of water and mix and stir, control the pH of the slurry to 9.5, the stirring speed to 25rpm, and the stirring time to 15min; the alkali activator is selected from water glass with a modulus of 2.0; the liquid-solid ratio of the slurry in step (5) is controlled to be 0.18; the temperature of the slurry during the stirring process is controlled to be 20℃; the slump expansion of the slurry is controlled to be 160mm.
[0168] (6) Aging and curing steps
[0169] The obtained slurry was aged at 20°C for 4 hours and then naturally stacked. During the aging process, the water content of the system was controlled at 18 wt%. After the aging was completed, the porosity of the solidified body was controlled at 15%.
[0170] (7) Maintenance steps
[0171] The desulfurized gypsum slag was cured at 25℃ and 70% relative humidity for 3 days to obtain a stable solidified product of heavy metals.
[0172] Test method:
[0173] I. Basic Composition of Test Raw Materials
[0174] The desulfurization gypsum residue used is taken from the wet desulfurization system of a coal-fired power plant, and its main components are as follows:
[0175] project content <![CDATA[CaSO4·2H2O]]> 72.4wt% <![CDATA[SiO2]]> 8.6wt% <![CDATA[Al2O3]]> 4.2wt% <![CDATA[Fe2O3]]> 2.8wt% Cl⁻ 0.91wt% Pb 426mg / kg Cd 58mg / kg Cr 215mg / kg Hg 7.8 mg / kg
[0176] II. TCLP Leaching Toxicity Test
[0177] The tests were conducted in accordance with the "HJ / T 300-2007 Solid Waste Leaching Toxicity Leaching Method - Acetic Acid Buffer Solution Method".
[0178] Test steps
[0179] The sample was crushed and passed through a 9.5mm sieve;
[0180] Prepare an acetate buffer solution with a pH of 2.64 ± 0.05;
[0181] Add the extract at a liquid-to-solid ratio of 20:1;
[0182] Shake at 30 rpm for 18 hours at 23±2℃;
[0183] After filtration, the concentrations of Pb, Cd, Cr, and Hg were determined by ICP-OES.
[0184] Table 1 Test Results
[0185] sample Pb (mg / L) Cd (mg / L) Cr (mg / L) Hg (mg / L) Example 1 0.38 0.07 0.31 0.011 Example 2 0.30 0.05 0.25 0.009 Example 3 0.24 0.05 0.20 0.008 Example 4 0.19 0.04 0.16 0.006 Comparative Example 1 0.64 0.20 0.60 0.024 Comparative Example 2 0.48 0.13 0.48 0.016 Comparative Example 3 0.44 0.11 0.42 0.014
[0186] By comparing the leaching toxicity data of each set of examples and comparative examples, it is clear that the sulfurization-chelation-gelation composite curing system constructed in this invention, combined with the independently developed sulfurization stabilizing synergist, can significantly reduce the leaching concentration of heavy metals such as lead, cadmium, chromium, and mercury in desulfurized gypsum slag. The heavy metal stabilization curing effect is far superior to that of traditional curing processes, and the two core components of the synergist play an indispensable synergistic role.
[0187] Among them, the primary and secondary amine functional groups in triethylenetetramine can effectively activate the sulfidation reaction system, improve the utilization rate of sulfidation agents, and enhance the precipitation effect of heavy metal sulfidation. At the same time, it can assist in fixing trace amounts of free heavy metals through adsorption and complexation, solving the defects of insufficient reaction and low agent utilization in traditional sulfidation. The carbon-carbon double bonds of the acrylate component can cross-link with the carboxylate group to form a film, which can encapsulate and seal the sulfidation precipitate and chelate products, block the internal seepage pores of the material, block the leaching of heavy metals from the transport path, and significantly improve the curing stability. With the catalytic regulation of sodium bicarbonate, the activity of each functional group of the synergist can be maximized, allowing multiple curing mechanisms to fully couple and take effect.
[0188] Compared to the comparative examples that did not use this synergistic system or the complete synergistic system, the leaching indicators of various heavy metals in each embodiment were significantly optimized. Furthermore, as the synergist's effect was fully realized, the curing effect continued to improve, and the degree of heavy metal stabilization was higher. The test results fully demonstrate that the synergistic effect of the multifunctional groups of the sulfurization stabilizing synergist is the core key to achieving deep harmlessness and long-term stable curing of desulfurized gypsum slag. The entire process exhibits excellent curing effect and stable performance, possessing extremely strong industrial practical value.
[0189] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for stabilizing and solidifying heavy metals in desulfurized gypsum slag, characterized in that, Includes the following steps: (1) Pretreatment steps: By weight, 100 parts of desulfurized gypsum slag were crushed, screened, and dried at low temperature. The particle size of the desulfurized gypsum slag was controlled to be 0.05-2 mm and the moisture content was 8-15%. The calcium sulfate dihydrate content in the desulfurized gypsum slag was 55-85 wt%. (2) Preparation steps of the gel stabilization system: By weight, 18-32 parts of granulated blast furnace slag powder, 8-18 parts of fly ash, 4-10 parts of silicate cement, and 1.5-4 parts of quicklime are added to the desulfurized gypsum slag and mixed. (3) Heavy metal sulfidation stabilization steps: By weight, add 0.8 to 2.5 parts of sodium sulfide and 0.3 to 1.2 parts of sodium thiosulfate as sulfide stabilizers, and then add 0.1 to 0.5 parts of sulfide stabilizing synergist. (4) Chelation and curing step: Add 0.3 to 1.5 parts by weight of an organic sulfur chelating agent, wherein the organic sulfur chelating agent is selected from one or more of sodium dithiocarbamate, trithiotriazine trisodium salt TMT-15, and sodium mercaptoacetate. (5) Alkali activation and mixing steps: Add 2-6 parts by weight of alkali activator and 18-30 parts by weight of water and mix. Control the pH of the slurry to be 9.5-11.8, the stirring speed to be 25-60 rpm, and the stirring time to be 15-40 min. (6) Aging and curing steps: The obtained slurry is aged at 20-35℃ for 4-18 hours, and then pressed into shape or naturally stacked. (7) Maintenance steps: The desulfurized gypsum slag was cured at 25–55℃ and 70–95% relative humidity for 3–14 days to obtain a stable solidified product of heavy metals.
2. The method for stabilizing and solidifying heavy metals in desulfurized gypsum slag according to claim 1, characterized in that: The desulfurized gypsum slag originates from one or more of the following systems: limestone-gypsum wet desulfurization system of coal-fired power plant, flue gas desulfurization system of iron and steel sintering, or flue gas desulfurization system of non-ferrous metal smelting; the Pb content in the desulfurized gypsum slag is 50-800 mg / kg, the Cd content is 5-120 mg / kg, and the Cr content is 20-500 mg / kg.
3. The method for stabilizing and solidifying heavy metals in desulfurized gypsum slag according to claim 1, characterized in that: The granulated blast furnace slag powder has a specific surface area of 380–520 m². 2 / kg, with an activity index of 95-110%; the fly ash is Class II fly ash, with a total SiO2 and Al2O3 content of 65-88wt%.
4. The method for stabilizing and solidifying heavy metals in desulfurized gypsum slag according to claim 1, characterized in that: The silicate cement is P.O42.5 ordinary silicate cement or P.SA32.5 slag silicate cement; the CaO content in the quicklime is not less than 85wt%.
5. The method for stabilizing and solidifying heavy metals in desulfurized gypsum slag according to claim 1, characterized in that: The sodium sulfide is Na2S·9H2O with a purity ≥60wt%; the sodium thiosulfate is Na2S2O3·5H2O with a purity ≥98wt%.
6. The method for stabilizing and solidifying heavy metals in desulfurized gypsum slag according to claim 1, characterized in that: The preparation method of the sulfurization stabilizer is as follows: By weight, 29-53 parts of triethylenetetramine distillation residue and 145-265 parts of acrylate industrial wastewater are mixed evenly, and 0.12-0.55 parts of sodium bicarbonate are added as a weak base addition catalyst. The mixture is stirred and reacted at a constant temperature of 58-78℃ for 70-100 minutes. After the reaction is completed, the mixture is dried under vacuum at a constant temperature and ground at room temperature to obtain the sulfide stabilizing synergist.
7. The method for stabilizing and solidifying heavy metals in desulfurized gypsum slag according to claim 1, characterized in that: The sodium dithiocarbamate has a purity of 85–98 wt%; the trisodium trithiotriazine salt content in TMT-15 is 12–18 wt%.
8. The method for stabilizing and solidifying heavy metals in desulfurized gypsum slag according to claim 1, characterized in that: The alkaline activator is selected from one or more of water glass, sodium hydroxide, and sodium carbonate with a modulus of 2.0 to 3.
3.
9. The method for stabilizing and solidifying heavy metals in desulfurized gypsum slag according to claim 1, characterized in that: In step (5), the liquid-to-solid ratio of the slurry is controlled at 0.18 to 0.30; the temperature of the slurry during the stirring process is controlled at 20 to 45°C; and the slump expansion of the slurry is controlled at 160 to 260 mm.
10. The method for stabilizing and solidifying heavy metals in desulfurized gypsum slag according to claim 1, characterized in that: In step (6), the pressing pressure is 3-12 MPa; the moisture content of the system is controlled to be 18-28 wt% during aging; and the porosity of the solidified body is controlled to be 15-35% after aging.
Citation Information
Patent Citations
Method for stabilizing and immobilizing cadmium in heavy metal pollution deposition by utilizing flue gas desulfurization gypsum
CN101746934A
Complex innocent treatment method for heavy metal gypsum
CN103495271A
Method for preparing geopolymer gelled material from heavy metal gypsum
CN103641346A
Permanent heavy metal waste curing method
CN105130363A
A method for resource utilization of arsenic-containing desulfurized gypsum residue
CN109231859B